Fast Holonomic Quantum Computation on Superconducting Circuits With Optimal Control. Issue 3 (23rd January 2020) - Li, Sai; Chen, Tao; Xue, Zheng‐Yuan
Abstract: Geometric phases induced in quantum evolutions have built‐in noise‐resilient characters, and thus can find applications in many robust quantum manipulation tasks. Here, a feasible and fast scheme for universal quantum computation on superconducting circuits with nonadiabatic non‐Abelian geometric phases is proposed, using resonant interaction of three‐level quantum system. In this scheme, arbitrary single‐qubit quantum gates can be implemented in a single‐loop scenario by shaping both the amplitudes and phases of the two driving microwave fields resonantly coupled to a transmon device. Moreover, nontrivial two‐qubit gates can also be realized with an auxiliary transmon simultaneously coupled to the two target transmons in an effective resonant way. In particular, this proposal can be compatible to various optimal control techniques, which further enhances the robustness of the quantum operations. Therefore, this proposal represents a promising way toward fault‐tolerant quantum computation on solid‐state quantum circuits. Abstract : Geometric phases have built‐in noise‐resilient characters, and thus are promising for robust quantum information processing. Now, a fast scheme for holonomic quantum computation on superconducting circuits is proposed, which is also compatible to optimal control techniques, and thus can further enhance the gate robustness. Therefore, it represents a promising way toward fault‐tolerant quantum computation on solid‐state quantum circuits.